Ontological framework for trust and reputation for DBE - Hammadi, Adil; Hussain, Farookh Khadeer; Chang, Elizabeth; Dillon, Tharam S.; Ali, S. (Institute of Electrical and Electronics Engineers (IEEE), 2008)
Today's e-Businesses rely heavily on trust and reputation systems. These systems are key indicators for businesses performance. Businesses that interact with each other for their business needs form a Digital Business Ecosystem (DBE). Members ofDBE need to know the trust and reputation value of each other before the start of business interactions. The feedback meclwnism is needed so that members of DBE form a unanimous opinion about any specific member of the community and based their business interactions on this opinion. We present an ontological framework that will combine the opinions from aU different trust and reputation databases for a specific member of a domain and gives the knowledge representation on the bases ofcombined opinion. We call this ontological framework feedback ontology.